2020
DOI: 10.1136/bmjresp-2020-000598
|View full text |Cite
|
Sign up to set email alerts
|

ILD-specific health-related quality of life in systemic sclerosis-associated ILD compared with IPF

Abstract: IntroductionIdiopathic pulmonary fibrosis (IPF) and systemic sclerosis-associated interstitial lung disease (SSc-ILD) are fibrotic ILDs with divergent disease populations. Little is known about health-related quality of life (HRQL) in SSc-ILD relative to IPF.MethodsWe used the Kings Brief Interstitial Lung Disease Questionnaire (K-BILD) to compare HRQL in a cross-sectional study of 57 patients with IPF and 29 patients with SSc-ILD. Analysis of covariance was used to adjust for age, gender and lung function.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The most likely explanation is the milder disease severity in our patient population, as evidenced by the higher FVC and DLCO %pred values compared with other studies, with almost two-thirds of our patients being GAP Stage I ( 25 ). Consistent with other studies, IPF patients have the poorest HRQL scores in terms of EQ5D-3L utility value, K-BILD total, ‘psychological’, ‘breathlessness and activities domain’ compared to CTD-ILD and other ILD patients ( 26 , 27 ). This could partly be explained by the lower DLCO values in IPF patients, which was a significant determinant of poor HRQL in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The most likely explanation is the milder disease severity in our patient population, as evidenced by the higher FVC and DLCO %pred values compared with other studies, with almost two-thirds of our patients being GAP Stage I ( 25 ). Consistent with other studies, IPF patients have the poorest HRQL scores in terms of EQ5D-3L utility value, K-BILD total, ‘psychological’, ‘breathlessness and activities domain’ compared to CTD-ILD and other ILD patients ( 26 , 27 ). This could partly be explained by the lower DLCO values in IPF patients, which was a significant determinant of poor HRQL in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies showed a significant correlation between the K-Bild score and the FVC, however they have included patients with Idiopathic pulmonary fibrosis who had a much lower FVC. 29 In the INBUILD trial a significant improvement was reached for FVC but K-BILD score was not significantly different in the treated and control group. 30 In our study, the EQ-5D-5L score increased significantly by 0.03 for 10% increase of the FVC.…”
Section: Discussionmentioning
confidence: 94%
“…At the baseline, and every 4 weeks after that, during their visit to IPDV’s outpatient clinics, the patients were asked to complete the K-BILD health status questionnaire, which had previously been validated to assess the health-related quality of life of ILDs patients [ 22 , 23 ], and was used as a PROs in several studies with ILDs patients [ 24 , 25 ]. This questionnaire included15 questions that evaluate three aspects of the patient’s functioning: breathlessness and activities, psychological functioning, and chest symptoms.…”
Section: Methodsmentioning
confidence: 99%